If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 7 = 35 Reorder the terms: 7 + 6x = 35 Solving 7 + 6x = 35 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 6x = 35 + -7 Combine like terms: 7 + -7 = 0 0 + 6x = 35 + -7 6x = 35 + -7 Combine like terms: 35 + -7 = 28 6x = 28 Divide each side by '6'. x = 4.666666667 Simplifying x = 4.666666667
| 3t-9t=-102 | | 7n+2=14 | | 7n+2=28 | | 9x-3=24 | | 9a-6=24 | | 9a-6=54 | | 3x-6=24 | | 4x+6=42 | | 7x+9=35 | | 7x+9=45 | | 2(3u+7)=4(3-2u) | | I=-217453+109x | | I=109x-217453 | | -3x+14=2 | | 10x+5=12x-1 | | 4a+6=30 | | 4a+6=35 | | 4x+2=6-2 | | 8(3x-9)=4(6x+6) | | 6x-3=39 | | 12a+24=48 | | 3(5z-1)-3(z+7)=7(z+1) | | X*17=-13 | | 9-3(-8)+4= | | -4(2-y)+3y=3(y-4) | | -94.8+b-43.161=-168.05 | | 6x-(2x+3)=1 | | 5.9x+3.5=15.3 | | 5.9+3.5=15.3 | | 9x-28=2x | | -8-n=-3(2n-4) | | 4x+1=(x-16) |